ANALYSIS OF JOB SATISFACTION AND MOTIVATION OF AGRICULTURAL EXTENSION WORKERS ON PERFORMANCE IN EAST JAVA PROVINCE - Humaidi, Faisol; Soedarto, Teguh; Mubarokah, Mubarokah; Yuliati, Nuriah (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
In this paper, the researchers conducted the research to determine the relationship between satisfaction and job motivation. It was done by based on the partially or simultaneously on the performance of agricultural extension workers. That research was done in several Regencies in East Java, such as Lamongan, Nganjuk, and Pacitan. The type of research had used ex post facto, such as like a form of research in which can be assessed events. It has happened in the assessments of factual conditions in the field. The method in this research was used by doing several surveys. It had done by through interviews and filling out questionnaires. The research had taken parts to the location of research. The population was taken to all agricultural extension agents. It is totaling 215 people from these regencies as the object research. The location are such as Lamongan, Nganjuk and Pacitan district agriculture offices. The data was analyzed to get information from distributing questionnaires to agricultural extension workers from the three regencies using SPSS 26. The hypothesis analysis was carried out by using multiple linear regression analysis. The results of hypothesis testing shown that the job satisfaction has significant effect on the performance of agricultural extension workers. The jobs motivation have a positive and significant effect on the performance of the instructor; simultaneously job satisfaction and performancing have a positive significant effect on the performance of agricultural extension workers.